The Great Cooper River Bridge - Annan, Jason, 1974- (Book collections on Project MUSE., 2002)
From the doldrums of the Depression to the growth of the 1990s, the Cooper River Bridge played a vital role in Charleston's transformation from an impoverished, isolated city to a vibrant and prosperous metropolis. Now obsolete and no longer adequately serving the needs of the Charleston area, the "old" Cooper River Bridge, and the "new" Silas N. Pearman Bridge-the Cooper River Bridge's larger sister structure that was erected in 1966-will be replaced. Funding, design, and construction are presently underway to replace the old structure with a single, modern bridge. The two original bridges have become true emblems of Charleston, much like the Eiffel Tower of Paris or the Golden Gate Bridge of San Francisco. With their removal, Charleston will lose two of its most significant landmarks. The Great Cooper River Bridge provides the complete history of this architectural icon, exploring how early twentieth-century Charleston helped shape the bridge, and how the bridge subsequently shaped the city. With more than eighty photographs, this illustrated volume documents a remarkable engineering feat and a distinctive structure before it becomes a memory.